Pengaruh Pendidikan Agama Islam Terhadap Perilaku Akhlak Siswa (Karakter) - H. Suhada; Arief Saptono; Ageng Setiani Rafika (UNIVERSITAS RAHARJA, 2018)
Description of Islamic Education on Student Moral Pattern (karakater) SMPN 23 Kota TangerangThis study is motivated by problems or junior high school students who are not in accordance with the students, because there are differences in students, smoking is not polite, rude, skipping school, lazy learning and others. The problem revealed in this study is how the benefits of Islamic religious education for students. The goal to be achieved is to know the meaning of Islamic religious education in the form of moral behavior (character) as the quality of learning. This research is a quantitative research with correlational type. The subjects of the study were students of SMPN 23 Tangerang class 8 and grade 9 of academic year 2013/2014 from 105 students from population 1425 students. Analysis of learning variable are good and give a significant effect on the quality of learning.